Quality of life and compliance with fluid restriction among hemodialysis patients in Hospital Universiti Sains Malaysia - Mohamad, Siti Aniza (Universiti Sains Malaysia, 2023)
A cross-sectional study was carried out to study the quality of life and compliance with fluid restriction among hemodialysis patients in Hospital Universiti Sains Malaysia. As the increasing of hemodialysis patients over the years in Malaysia, it is crucial all hemodialysis patients to comply the treatment regimens of hemodialysis (diet, fluid restriction, medication) to stabilize their quality of life. The questionnaire used in this study was World Health Organization Quality of Life Brief Version (WHOQOL-BREF) adapted from World Health Organization and compliance of fluid restriction by Hirmawaty (2014). A total of 50 hemodialysis patients in Hospital USM who fulfilled the inclusion and exclusion criteria were selected randomly. Data collection were statically analyzed using SPSS software version 27.0. Fisher’s exact test was used for data analysis. As for the quality of life and compliance of fluid restriction score, the results show 34 patients (68%) in good level and 20 patients (40%) in low compliance respectively. There was no relationship between quality of life and compliance of fluid restriction (p value = 0.836). Moreover, there was a significant relationship between marital status and compliance of fluid restriction (p value = 0.026), the results show 15 patients are in the low compliance level. Aside from that, there were no relationship between other sociodemographic factors and quality of life and compliance of fluid restriction. In conclusion, patients’ knowledge and practice of treatment regimens has to be enhanced and improved so they will be knowledgeable and able to comply to treatment regimens thus increasing their quality of life.